2011
DOI: 10.2514/1.a32040
|View full text |Cite
|
Sign up to set email alerts
|

Costate Estimation using Multiple-Interval Pseudospectral Methods

Abstract: A method is presented for costate estimation in nonlinear optimal control problems using multiple-interval collocation at Legendre-Gauss or Legendre-Gauss-Radau points. Transformations from the Lagrange multipliers of the nonlinear programming problem to the costate of the continuous-time optimal control problem are given. When the optimal costate is continuous, the transformed adjoint systems of the nonlinear programming problems are discrete representations of the continuous-time first-order optimality condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…For problems where the solutions are infinitely smooth and well behaved, a pseudospectral method has a simple structure and converges at an exponential rate . Most importantly, when the optimal costate is continuous, the results presented in show that, for the GPM and RPM, the transformed adjoint systems of the NLP are discrete representations of the continuous‐time first‐order optimality conditions and accurate costate estimations can be obtained from the Karush–Kuhn–Tucker (KKT) multipliers of the NLP. However, for problems with either nonsmooth solutions or nonsmooth problem formulations, applying the pseudospectral methods directly to solve these problems may result in low convergence speed and accuracy.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For problems where the solutions are infinitely smooth and well behaved, a pseudospectral method has a simple structure and converges at an exponential rate . Most importantly, when the optimal costate is continuous, the results presented in show that, for the GPM and RPM, the transformed adjoint systems of the NLP are discrete representations of the continuous‐time first‐order optimality conditions and accurate costate estimations can be obtained from the Karush–Kuhn–Tucker (KKT) multipliers of the NLP. However, for problems with either nonsmooth solutions or nonsmooth problem formulations, applying the pseudospectral methods directly to solve these problems may result in low convergence speed and accuracy.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, development has increased in pseudospectral methods, in which the collocation points are based on accurate quadrature rules and the basic functions are typical Chebyshev or Lagrange polynomials . The most well‐developed pseudospectral methods are the Lobatto pseudospectral method , Gauss pseudospectral method (GPM) , and the Radau pseudospectral method (RPM) . Using pseudospectral collocation, the differential equations are converted into algebraic equations, which are generally more convenient to solve.…”
Section: Introductionmentioning
confidence: 99%
“…The number of terms in the infinite series is related to the order of the polynomial: a higher-order polynomial approximation will be more accurate. There are many papers that cover the detailed mathematics of orthogonal polynomials [26,44,4,33,58,28] and their use in trajectory optimization [29,62,18,30,19,53,3,57,23,24,15,21]. Here we will focus on the practical implementation details and on gaining a qualitative understanding of how orthogonal collocation works.…”
Section: B1 Full Solutionmentioning
confidence: 99%
“…Orthogonal collocation is similar to direct collocation, but it generally uses higher-order polynomials. The collocation points for these methods are located at the roots of an orthogonal polynomial, typically either Chebyshev or Legendre [15]. Increasing the accuracy of a solution is typically achieved by increasing either the number of trajectory segments or the order of the polynomial in each segment.…”
Section: Direct Multiple Shootingmentioning
confidence: 99%
“…The approach is motivated by the results of Ref. 35 where it was shown that the accuracy of the pseudospectral costate estimate can be quite poor due to discontinuities that arise in the presence of active state-inequality path constraints. The method developed in this paper utilizes a modified version of the Radau pseudospectral method.…”
Section: Introductionmentioning
confidence: 99%